PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DIVISI KESEKRETARIATAN PT PLN (PERSERO) DISTRIBUSI JAKARTA RAYA DAN TANGERANG - Megido Andreas; Maswir Maswir; Mawarta Onida (Politeknik Negeri Jakarta, 2017)
AbstractThis research aimed to analyze and determine the performance of employees in the Secretariat Division of PT PLN (Persero) Distribution of Jakarta and Tangerang using motivational variables are analyzed based on the theory of intrinsic motivation, according to Herzberg two-factor theory. This research was conducted to measure employee performance using several indicators, including the number (quantity) of work, quality of work, precision time, attendance, and cooperation ability. The method used in this research is the quantitative method with survey research and data collection through a questionnaire to the respondent. Processing data using a data analysis tool named SPSS (Statistical Package for the Social Sciences) version 21. The samples used in this study as many as 23 people. Based on the calculation simple linear regression analysis obtained regression equation Y = 5.113 + 0,894X. From the calculation of the coefficient of determination the influence of work motivation (Variable X) on the performance (Variable Y) is equal to 0.413 or 41.3%, while the remaining 0.587 or 58.7% is influenced by independent variables studied were: job satisfaction, stress, trust, justice, ethics, training and decision-making. From the calculation of significance test (partial test) can be obtained values (t count > t table), i.e. 3.844 > 1.721 that means Ha accepted and Ho rejected, so the hypothesis are